Spatiotemporal variation and sources of soil heavy metals along the lower reaches of Yangtze River, China. (March 2022) - Liu, Peng; Wu, Qiumei; Wang, Xinkai; Hu, Wenyou; Liu, Xiaoyan; Tian, Kang; Fan, Ya'nan; Xie, Enze; Zhao, Yongcun; Huang, Biao; Yoon, Seo Joon; Kwon, Bong-Oh; et al.
Abstract: Excessive accumulation of soil heavy metals (HMs) result in the deterioration of soil quality and reduction of agricultural productivity and safety. The accumulation status, temporal change, and sources of soil HMs were determined by large-scale field surveys in 2014 and 2019 in rapid urbanization and industrialization area along the lower reaches of the Yangtze River, China. Eighty-two surface soil samples were collected in 2014 and ninety-five surface soil samples and seven soil profiles (0–100 cm) were collected in 2019. The mean concentrations (in, mg kg −1 ) of As (10.17), Cd (0.33), Cr (86.38), Cu (38.22), Hg (0.11), Ni (37.67), Pb (43.95), and Zn (113.15) were greater than the corresponding background values. The concentrations of these 8 HMs significantly varied with site-specific distributions depending on nearby landscape patterns with decreasing order: agricultural soil around industrial > agricultural soil > fallow soil. Cd and Hg were found to be priority pollutants due to their greater accumulations in this study area. Combined analyses of principal component analysis and positive matrix factorization model addressed source apportionment of soil HMs. Industrial activities, parent materials, and agricultural and traffic activities were three major sources and their contributions were 35.56%, 35.20%, and 29.23%, respectively. The concentrations of soil As, Cd, Cr and Pb increased with time. This study elucidates how changes in land uses and time affect soil HMs and provides reasonable suggestions for the effective reduction of HM contamination in economically and industrially developed areas of China, and elsewhere. Graphical abstract: Image 1 Highlights: Cd and Hg were soil priority pollutants along the lower reaches of the YRD, China. Hot-spot areas of higher heavy metal concentration were distributed in the upper reaches. The concentration of soil As, Cd, Cr, and Pb increased from 2014 to 2019. Industrial activities primarily increased the degree of heavy metal accumulation in soils.